2000
DOI: 10.1152/ajpheart.2000.278.6.h1993
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glycogen storage on vascular smooth muscle metabolism

Abstract: The role of glycogen as an oxidative substrate for vascular smooth muscle (VSM) remains controversial. To elucidate the importance of glycogen as an oxidative substrate and the influence of glycogen flux on VSM substrate selection, we systematically altered glycogen levels and measured metabolism of glucose, acetate, and glycogen. Hog carotid arteries with glycogen contents ranging from 1 to 11 micromol/g were isometrically contracted in physiological salt solution containing 5 mM [1-(13)C]glucose and 1 mM [1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 23 publications
4
25
0
Order By: Relevance
“…Studies of VSM oxidative metabolism have demonstrated the importance of glucose as an oxidative substrate [1, 2]. In these experiments, the short-chain fatty acid acetate (1 m M ) was used to represent total plasma fatty acids.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of VSM oxidative metabolism have demonstrated the importance of glucose as an oxidative substrate [1, 2]. In these experiments, the short-chain fatty acid acetate (1 m M ) was used to represent total plasma fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…In these experiments, the short-chain fatty acid acetate (1 m M ) was used to represent total plasma fatty acids. In the presence of 5 m M glucose and with glycogen contents spanning the range reported in vivo for VSM (1–15 µmol/g), acetate comprises 30–50% of the substrates oxidized by VSM [1, 2]. However, this is probably an overestimate of the contribution of long-chain fatty acids to VSM oxidative metabolism, because short-chain fatty acids are oxidized to a greater extent than long-chain fatty acids [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A segregation can be explained by cytosolic "channeling" of metabolites from one enzyme to the next in a pathway. Such a channeling is known in vascular smooth muscle, where lactate formed by glycolysis is segregated from that formed by glycogenolysis (Allen and Hardin, 2000;Lynch and Paul, 1983). The channeling may not be restricted to the individual astrocyte in which lactate was produced.…”
Section: Which Cell Type Is the Predominant Producer Of Lactate In Thmentioning
confidence: 99%
“…Based on data from independent groups, it has previously been estimated that glycogen stores can maintain ATP production for 38 minutes in contracting pig carotid arteries. 32 However, in our setup, ATP levels were maintained for 3 hours under well-oxygenated conditions. This might be explained by the fact that the vessel segments were unstimulated in our experiments and could thus be expected to have a substantially lower energy demand than contracting arteries.…”
Section: Glycogen As An Energy Substratementioning
confidence: 99%